Correction: Sedentary behavior, physical activity, sleep duration and obesity risk: Mendelian randomization study. - Siqing Chen; Lili Yang; Yuting Yang; Wenmini Shi; Matthew Stults-Kolehmainen; Qiao Yuan; Chenchen Wang; Jing Ye (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0300074.].